2011
DOI: 10.1093/nar/gkr734
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Sox10 orchestrates activity of a neural crest-specific enhancer in the vicinity of its gene

Abstract: The Sox10 transcription factor is a central regulator of vertebrate neural crest and nervous system development. Its expression is likely controlled by multiple enhancer elements, among them U3 (alternatively known as MCS4). Here we analyze U3 activity to obtain deeper insights into Sox10 function and expression in the neural crest and its derivatives. U3 activity strongly depends on the presence of Sox10 that regulates its own expression as commonly observed for important developmental regulators. Sox10 bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 50 publications
9
87
0
Order By: Relevance
“…Furthermore, Sox10 was shown to directly regulate itself, consistent with its continuous expression in the migratory neural crest. This positive self-regulatory loop relies on synergistic activity with Tfap2a and FoxD3 (Wahlbuhl et al, 2012). That FoxD3 acts as a direct regulator of Sox10 in migratory cells is supported by another study that identified an intronic enhancer in the zebrafish sox10 locus, which contains FoxD3, Sox and LEF/TCF binding sites (Dutton et al, 2008).…”
Section: Regulatory Interactions In the Migratory Neural Crestmentioning
confidence: 87%
“…Furthermore, Sox10 was shown to directly regulate itself, consistent with its continuous expression in the migratory neural crest. This positive self-regulatory loop relies on synergistic activity with Tfap2a and FoxD3 (Wahlbuhl et al, 2012). That FoxD3 acts as a direct regulator of Sox10 in migratory cells is supported by another study that identified an intronic enhancer in the zebrafish sox10 locus, which contains FoxD3, Sox and LEF/TCF binding sites (Dutton et al, 2008).…”
Section: Regulatory Interactions In the Migratory Neural Crestmentioning
confidence: 87%
“…For Schwann-cell-specific enhancers that are activated by Sox10, there seems to be no strict reliance on dimeric binding. Some Schwann-cell-specific enhancers only contain dimer sites and crucially depend on them (i.e., the Oct6 SCE) (Jagalur et al, 2011), whereas others contain only monomeric sites (i.e., the Dhh enhancer), yet others carry both monomeric and dimeric sites and need both for their activity (i.e., Krox20 myelinating Schwann cell enhancer, U3 enhancer of the Sox10 gene) (Reiprich et al, 2010;Wahlbuhl et al, 2012). Considering that Sox10 monomers affect the overall topology of the enhancer in a different way than dimers, the most likely explanation is that each enhancer contains the type of site that is best suited at its specific position to guarantee the multiprotein complex formation of the enhanceosome.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments indicate that deletion of this domain does not reduce the transactivation potential of Sox10, but may interfere with its ability to function synergistically with other transcription factors (Reiprich et al, 2008). This argues that the K2 domain likely functions as another interface for protein interactions, although the only interactor so far identified is AP2α (Figure 1) (Wahlbuhl et al, 2011). The last domain that is shared between SoxE proteins is the transactivation domain at the carboxyterminal end ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%